Island Tourism In Malaysia The Not So Good News. - Mohamed, Badaruddin; Mat Som, Ahmad Puad; Jusoh, Jamil; Kong, Yew Wong (2006)
Tourism is regarded as an important sector to the Malaysian economy. Thanks to intense worldwide promotion by Tourism Malaysia, tourism is reported to bring in almost RM30 Billion of income to the national coffer.